The predictive value of different reasons for saving and acquiring on hoarding disorder symptoms - Dozier, Mary E. (J Obsessive Compuls Relat Disord, 2014)
Few studies to date have studied the particular reasons endorsed by individuals with hoarding disorder (HD) for why they save or acquire certain objects. Understanding how reasons for saving and acquiring objects influence hoarding severity and the degree to which the relationship depends on gender or age differences can have implications for the treatment of HD. The current study looked at reasons for saving and acquiring in 84 individuals diagnosed with HD. Consideration of the usefulness of an object as a reason for saving was the most consistently uniquely predictive of all of the reasons examined for saving and acquisition when controlling for gender differences and other endorsed reasons. These results may suggest that targeting specific reasons for saving and acquiring may be an efficient way to reduce hoarding severity, specifically related to ideas of utility and waste.